Comparative Study of Prevalence of type-2 Diabetes Mellitus in Various Demographic Regions of Andhra Pradesh, India: A Population-Based Study - Pangi Vijaya Nirmala, PhD; Mani Gudivada, PhD; Chikkam Vijaya Lashmi, PhD (Global Health and Education Projects, Inc., 2016)
Background and Introduction: Diabetes is increasing at alarming rate among Indians especially South Indians with prevalence of diabetes mellitus (PODM) varying in populations of different regions. This study assesses PODM in three geographical areas, namely: tribal, semi-urban, and urban, and to compare the diabetes risk in northern coastal districts of Andhra Pradesh state in India. Methodology: A random sampling method was followed to study the prevalence of diabetes in about 3,000 individuals of age group between 15-68 years, selecting 1,000 individuals from each area. As per 1988 World Health Organization criteria and norms, diabetes mellitus was diagnosed on the basis of 75-g oral glucose tolerance test (OGT). Statistical analyses were conducted using Microsoft Excel 2007. Results: The analysis of the study indicates that 35.5% individuals were identified to be diabetic, especially 7.8% from Tribal area, 12.5% from semi-urban and 15.1% from urban area. Conclusion and Global Health Implications: The study indicates that people in urban area were more prone to type-2 diabetes than those in Tribal and semi-urban area. New cases of diabetes were reported in tribal areas when compared to semi-urban and urban areas indicating that rural people were not spared from diabetes. The study also indicates that there is an increase in the prevalence of diabetes in tribal area of Andhra Pradesh State of India when compared to previous studies. Key words: Diabetes Mellitus (DM) • Prevalence of Diabetes Mellitus (PODM) • Oral Glucose Tolerance Test (OGT) Copyright © 2016 Nirmala et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.